The sensational impact of YouTube advertising on purchase intentions based on boosting e-commerce sales in Jabodetabek - Yokie Radnan Kristiyono; Thomas Pratama; Juniarty Siahaan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Technology and the internet are responsible for changing the functional patterns of society, shifting the economy, and improving social factors. This shows that electronic commerce (e-commerce) is one of the methods companies implement in acquiring a competitive advantage, through advertising and word-of-mouth. From this context, YouTube is a popular social media platform, which provides consumers with streaming entertainment and digital information. Most e-commerce YouTube advertisements are also shared by the majority of subscribers to their peers/colleagues, leading to increased brand awareness and effective purchase intention. Therefore, this study aims to empirically determine the influence of YouTube advertising and eWOM on the brand awareness of e-commerce platforms toward purchase intention, among millennial consumers in the Jabodetabek areas. An online questionnaire of the required quantitative data was implemented for information acquisition from a total of 165 participants, by using Partial Least Square as an analytic tool. The results showed that Electronic Commerce Advertisement Value on YouTube and eWOM strongly and positively impacted brand awareness, leading to a great and emphatic correlation toward purchase intention on e-commerce platforms.